2019
DOI: 10.1371/journal.pone.0221422
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of sulfotransferase genes and their responses to abiotic stresses in Chinese cabbage (Brassica rapa L.)

Abstract: Sulfotransferases (SOTs; EC 2.8.2.-), which are widespread from prokaryotes to eukaryotes, constitute a multi-protein family that plays crucial roles in plant growth, development and stress adaptation. However, this family has not been systemically investigated in Brassica rapa . Here, a genome-wide systemic analysis of SOT genes in B . rapa subsp. pekinensis , a globally cultivated vegetable, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Seven sulfotransferases ( SOT ), enzymes catalyzing the sulfation process, were also increased after salt stress both in Adina and Zhaodong. The changes of the SOT s in our study are consistent with what is documented in transcriptional assays, such as the expression of AtSOT12 ( Hirschmann et al., 2014 ), BrSOT s ( Jin et al., 2019 ) and SjSOT s ( Lu et al., 2020 ) after exposure to salt stress. A leading hypothesis is that the sulfation of polysaccharides that causes the modification of the composition of cell walls is the main reason for increased salt tolerance in plants ( Hirschmann et al., 2014 ).…”
Section: Discussionsupporting
confidence: 90%
“…Seven sulfotransferases ( SOT ), enzymes catalyzing the sulfation process, were also increased after salt stress both in Adina and Zhaodong. The changes of the SOT s in our study are consistent with what is documented in transcriptional assays, such as the expression of AtSOT12 ( Hirschmann et al., 2014 ), BrSOT s ( Jin et al., 2019 ) and SjSOT s ( Lu et al., 2020 ) after exposure to salt stress. A leading hypothesis is that the sulfation of polysaccharides that causes the modification of the composition of cell walls is the main reason for increased salt tolerance in plants ( Hirschmann et al., 2014 ).…”
Section: Discussionsupporting
confidence: 90%
“…Other enzymes associated with secondary metabolism were FLAVONOL SULFOTRANSFERASE-LIKE, PHENYLALANINE AMMONIA-LYASE, ANTHOCYANIDIN 3-O-GLUCOSYLTRANSFERASE 5-LIKE, and ANTHOCYANIDIN SYNTHASE. These enzymes are involved in defense against abiotic and biotic stresses (Landi et al ., 2015; Zhang & Liu, 2015; Qiu et al ., 2016; Jin et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…( Leitão et al., 2021 ) indicated that accumulation of sulfurtransferase was increased under stress induced by pharmaceutical contamination. Also, several studied illustrated that sulfurtransferases play a main role in plant response to abiotic stress such as osmotic, salt and hormone stress ( Jin et al., 2019 ). Overall, increased expression of cytosolic sulfotransferase 4 and thiosulfate/3-mercaptopyruvate sulfurtransferase 1 indicated a wide range of changes associated with osmotic stress.…”
Section: Discussionmentioning
confidence: 99%